MENUMBUHKAN MINAT LITERASI ANAK SEJAK DINI MELALUI POJOK LITERASI DI PAUD KHAIRUL UMMAH: Fostering Children's Interest in Literacy from an Early Age Through the Creation of a Literacy Corner for PAUD Khairul Ummah - Nugroho, Bayu Aji; Dewanto, Bayu (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2022)
Abstract: The Mulawarman University team carried out community service located in Graha Indah Village. Low literacy culture is the main focus of the work program in Graha Indah Village. Therefore, one of the work programs that will be carried out is the Creation of a Literacy Corner which functions as a means of literacy facilities and forms reading habits for children from an early age. Observation is the initial stage of implementing this work program, then preparation, implementation, and evaluation. This is done for efforts to form reading adaptation in order to grow and increase interest in reading in early childhood. The work program carried out resulted in the growth of children's interest in reading at PAUD Khairul Ummah. The children of PAUD Khairul Ummah looked very enthusiastic during the reading assistance activities. As an effort to intensify the Indonesian literacy movement, it is hoped that the activities that have been welded will foster children's interest in reading. Keywords: literacy corner; reading interest; community service.   Abstrak: Tim Universtas Mulawarman melakukan pengabdian masyarakat yang berlokasi di Kelurahan Graha Indah. Budaya literasi yang rendah menjadi fokus utama program kerja di Kelurahan Graha Indah. Oleh karena itu, salah satu program kerja yang akan dilakukan yaitu Pembuatan Pojok Literasi yang berfungsi sebagai sarana fasilitas literasi, dan membentuk kebiasaan membaca bagi anak-anak sejak dini. Pengamatan merupakan tahapan awal pelaksanaan program kerja ini, selanjutnya persiapan, pelaksanaan, serta evaluasi. Hal ini dilakukan sebagai upaya pembentukan adaptasi membaca guna menumbuhkan dan meningkatkan minat baca pada anak-anak usia dini. Program kerja yang dilakukan menghasilkan tumbuhnya minat baca anak di PAUD Khairul Ummah. Anak-anak PAUD Khairul Ummah terlihat sangat antusias pada saat pelaksanaan kegiatan pendampingan baca. Sebagai upaya menggiatkan gerakan literasi Indonesia, diharapkan kegiatan yang telah dilaksanakan dapat menumbuhkan minat baca pada anak usia dini. Kata kunci: pojok literasi; minat baca; pengabdian masyarakat.